Findings of Hernia Repair Procedure in Iraqi Children: A Cross-Sectional Study - Ali Abdulhussein Sabri Al Edani; Adil Abdulmajeed Hassan; Waleed Khalid Ahmed Al-Jumaili (Recent Updates in Disease and Health Research Vol. 6, 2024)
Background: Inguinal herniorrhaphy with pediatric surgeons has been performed with more variability, according to prior investigations and their experience. One of the most prevalent conditions in children and young adults is an inguinal hernia. For full-term and preterm newborns, the estimated prevalence rates of inguinal hernia are 1-5% and 9-11%, correspondingly. Aim: This paper aims to analyze a cross-sectional study to detect the findings of hernia repair procedures in Iraqi children. Patients and Methods: This paper was conducted in different hospitals in Iraq from 15th September 2021 to 17th December 2021 as a cross-sectional study to analyze cross-sectional study to detect the findings of hernia in Iraqi children. This study contained 54 patients, which were separated into two kinds of groups. The first group included 27 patients who had open surgery, while the second group had 27 patients who were present patients who had laparoscopic surgery. The databases collected were analyzed and plotted by the SPSS program. Results and Discussion: In this study, we examine the results of two techniques for hernia repair in young girls and boys. The results showed that although laparoscopic surgery and open surgery had different post-operative problems, open surgery required less time to complete an inguinal hernia repair in patients than laparoscopic surgery did. The incidence of pre-operative and post-operative problems varied across the two research groups in our study. In comparison to previous studies, our study showed different results, which found the success of open surgery in comparing with laparoscopic surgery where the post-operative complications of open surgery were lower with laparoscopic surgery. Conclusion: The findings generally demonstrated that even though the preoperative and postoperative problems of the two repair techniques were very close to one another. However, when safety for hernia repair in children under six years old was taken into consideration, herniotomy opening surgery took a little less time to perform than laparoscopic surgery.